Genomic control process : development and evolution - Peter, Isabelle S.; Davidson, Eric H. (London, UK : Academic Press, 2015)
Genomic Control Process explores the biological phenomena around genomic regulatory systems that control and shape animal development processes, and which determine the nature of evolutionary processes that affect body plan. Unifying and simplifying the descriptions of development and evolution by focusing on the causality in these processes, it provides a comprehensive method of considering genomic control across diverse biological processes. This book is essential for graduate researchers in genomics, systems biology and molecular biology seeking to understand deep biological processes which regulate the structure of animals during development. Covers a vast area of current biological research to produce a genome oriented regulatory bioscience of animal life Places gene regulation, embryonic and postembryonic development, and evolution of the body plan in a unified conceptual frameworkProvides the conceptual keys to interpret a broad developmental and evolutionary landscape with precise experimental illustrations drawn from contemporary literatureIncludes a range of material, from developmental phenomenology to quantitative and logic models, from phylogenetics to the molecular biology of gene regulation, from animal models of all kinds to evidence of every relevant typeDemonstrates the causal power of system-level understanding of genomic control process.
Includes bibliographical references at the end of each chapters and index.
Vendor-supplied metadata.
Elsevier
Keywords: Developmental genetics; SCIENCE / Life Sciences / Genetics & Genomics; Developmental genetics; Electronic books; Electronic books